2017
DOI: 10.1016/j.neuropsychologia.2016.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Functional organization of the language network in three- and six-year-old children

Abstract: The organization of the language network undergoes continuous changes during development as children learn to understand sentences. In the present study, functional magnetic resonance imaging and behavioral measures were utilized to investigate functional activation and functional connectivity (FC) in three-year-old (3yo) and six-year-old (6yo) children during sentence comprehension. Transitive German sentences varying the word order (subject-initial and object-initial) with case marking were presented auditor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 64 publications
2
15
0
1
Order By: Relevance
“…In a more recent study, using similar stimulus material, the performance of 3-year-olds was considered at the individual level. It was found that 11 out of 21 children performed above chance for object-first sentences whereas 10 performed at chance ( Vissiennon, Friederici, Brauer, & Wu, 2017 ). Although indicating high behavioral variability around this age, these data provide the first evidence that children, even from the age of 3 years, start to use case-marking as a possible cue to help sentence interpretation.…”
Section: Processing Case Markers In Childrenmentioning
confidence: 96%
“…In a more recent study, using similar stimulus material, the performance of 3-year-olds was considered at the individual level. It was found that 11 out of 21 children performed above chance for object-first sentences whereas 10 performed at chance ( Vissiennon, Friederici, Brauer, & Wu, 2017 ). Although indicating high behavioral variability around this age, these data provide the first evidence that children, even from the age of 3 years, start to use case-marking as a possible cue to help sentence interpretation.…”
Section: Processing Case Markers In Childrenmentioning
confidence: 96%
“…This was not always the case in the left IFG however, in particular BA44. Increased activation in left BA45 but not BA44 is a pattern that is seen in the "developmental" stage of language learning in children or when processing is controlled rather than automatic (Jeon and Friederici, 2015;Vissiennon et al, 2017). We propose that the pattern of frontal activation we saw in our LAHP bilinguals was a function of degree of automaticity in L2.…”
Section: Resultsmentioning
confidence: 54%
“…Put another way: there is a reliance on BA44 in adult native language processing, which is considered to be highly automatic. In children however (and by extension L2 learners) language learning is still in "development" and there is greater reliance during this period on BA45, a more anterior part of the IFG (Hahne et al, 2004;Vissiennon et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When getting a language, the child is faced with a challenge to decode relationships between certain greeting entities, which require certain grammatical sayings and the thematic roles played by each entity. So that this can be done, the child must implement it linguistic cues and regularities provided by certain languages (Vissiennon, Friederic, Brauer, & Wu, 2016). Language mastery can be seen as a type of mastery of skills, just as in learning to ride a bicycle, play a musical instrument, or draw; and the need to gain knowledge about the abstract structure of language (Chater & Christianshen, 2018).…”
Section: Introductionmentioning
confidence: 99%